Transitions from pediatric to adult IBD care: Incorporating lessons from psychogastroenterology - Mendiolaza, Michelle L.; Feingold, Jordyn H.; Kaye-Kauderer, Halley P.; Dubinsky, Marla C.; Gorbenko, Ksenia O.; Keefer, Laurie A. (Frontiers in Gastroenterology, 2022)
The transition from pediatric to adult gastroenterology care for adolescents with inflammatory bowel disease (IBD) is a critical period associated with poor disease outcomes and high medical costs. Burdens such as the discontinuity of care when transitioning from one provider to another are amplified by poor coping and psychosocial factors. However, existing research on the topic of health care transitions has centered largely on disease knowledge and competencies that young adults ought to master and self-manage, while largely disregarding the broader psychosocial context and impacts of IBD on daily functioning. Findings from a recent mixed-methods pilot study of transition-aged adolescents with IBD and their parents highlight the importance of acknowledging the psychosocial needs of adolescents with IBD and their families throughout the transition process, which include understanding the gut-brain axis, optimizing social support and mental health resources, and maintaining optimism and positivity. In this review, we expand upon the findings from this pilot study, synthesize the latest research in psychogastroenterology and pediatric-to-adult transitions in IBD, and provide five patient-centered interventions that may be implemented in clinical settings, in anticipation of, and during the patient transition experience. These interventions are rooted in positive psychology and cognitive-behavioral principles and are designed for adolescents with IBD to complete with input from their families and health care professionals.